Advances in Vaccine Development of the Emerging Novel Genotype Fowl Adenovirus 4 - Liu, Aijing; Zhang, Yu; Cui, Hongyu; Wang, Xiaomei; Gao, Yulong; Pan, Qing (Frontiers in Immunology, 2022)
Fowl adenovirus (FAdV) was first reported in Angara Goth, Pakistan, in 1987. For this reason, it is also known as "Angara disease." It was later reported in China, Japan, South Korea, India, the United States, Canada, and other countries and regions, causing huge economic losses in the poultry industry worldwide. Notably, since June 2015, a natural outbreak of severe hydropericardium hepatitis syndrome (HHS), associated with a hypervirulent novel-genotype FAdV-4 infection, has emerged in most provinces of China. The novel virus FAdV-4 spread rapidly and induced a 30-100% mortality rate, causing huge economic losses and threatening the green and healthy poultry breeding industry. Vaccines against FAdV-4, especially the emerging novel genotype, play a critical role and will be the most efficient tool for preventing and controlling HHS. Various types of FAdV-4 vaccines have been developed and evaluated, such as inactivated, live-attenuated, subunit, and combined vaccines. They have made great contributions to the control of HHS, but the details of cross-protection within FAdVs and the immunogenicity of different vaccines require further investigation. This review highlights the recent advances in developing the FAdV-4 vaccine and promising new vaccines for future research.